A case series of rapidly growing mycobacterial catheter-related bloodstream infections among immunocompetent patients. (December 2020) - Mizusawa, Masako; Vindenes, Tine; Buckley, Sarah; Armstrong, Catharina
Abstract: Rapidly growing mycobacteria (RGM) are ubiquitous in the environment and can cause a variety of human infections. Catheter-related bloodstream infections (CRBSI) caused by RGM have been reported predominantly among immunocompromised patients. Removal of central lines and antimicrobial therapy with at least 2 active agents are generally recommended for immunocompromised patients. RGM bloodstream infections (BSIs) are rare in immunocompetent patients and clinical data are very limited. Retrospective medical record review was conducted on patients with blood cultures positive for RGM from July 2012 through March 2015 at Lemuel Shattuck Hospital, a public teaching hospital in Jamaica Plain, Massachusetts, United States. RGM was suspected by presence of beaded Gram-positive bacilli on Gram staining of positive conventional blood cultures and it was confirmed as RGM by Massachusetts State Public Health Laboratory. Nineteen episodes of RGM BSI were identified in 17 patients who had no known immunocompromised conditions that predispose them to opportunistic pathogens. They were predominantly young male with history of intravenous drug use. Peripherally inserted central catheter (PICC) was present in all episodes of RGM BSI and 74% of them clinically improved with PICC removal alone without specific antibiotic therapy for RGM. They were followed up for median duration of 45 days (interquartile range 25–385). The patients remained alive and asymptomatic until the end of follow-up periods. In immunocompetent patients, removal of catheters alone without adding specific antibiotics may be sufficient for RGM CRBSI.